2015
DOI: 10.1155/2015/102054
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lactate Levels Increase during Hyperinsulinemic Euglycemic Clamp and Oral Glucose Tolerance Test

Abstract: Insulin resistance, which plays a central role in the pathogenesis of type 2 diabetes (T2D), is an early indicator that heralds the occurrence of T2D. It is imperative to understand the metabolic changes that occur at the cellular level in the early stages of insulin resistance. The objective of this study was to determine the pattern of circulating lactate levels during oral glucose tolerance test (OGTT) and hyperinsulinemic euglycemic clamp (HIEC) study in normal nondiabetic subjects. Lactate and glycerol we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
(24 reference statements)
2
39
0
3
Order By: Relevance
“…The relative contribution of this shuttle as a neuronal fuel source compared with neuronal glucose uptake via glucose transporters is still debated, although it is clear that neurons can use lactate to fuel oxidative phosphorylation and generate ATP during periods of high energy demand 87 . Hyperinsulinaemia is reported to increase peripheral lactate levels, which in turn could affect the net flux of lactate across the BBB and affect energy metabolism within the brain 88 ; therefore, the effect of insulin levels on lactate could have implications for brain functioning. Astrocytes bind insulin with high affinity 89 and express IRS1, IRS2 and downstream signalling molecules AKT and MAPK.…”
Section: Insulin and The Brainmentioning
confidence: 99%
“…The relative contribution of this shuttle as a neuronal fuel source compared with neuronal glucose uptake via glucose transporters is still debated, although it is clear that neurons can use lactate to fuel oxidative phosphorylation and generate ATP during periods of high energy demand 87 . Hyperinsulinaemia is reported to increase peripheral lactate levels, which in turn could affect the net flux of lactate across the BBB and affect energy metabolism within the brain 88 ; therefore, the effect of insulin levels on lactate could have implications for brain functioning. Astrocytes bind insulin with high affinity 89 and express IRS1, IRS2 and downstream signalling molecules AKT and MAPK.…”
Section: Insulin and The Brainmentioning
confidence: 99%
“…Lactate metabolism is directly implicated in the gluconeogenesis, indirectly in the TCA cycle and in the respiratory chain, which are metabolic pathways implicated in carbohydrate metabolism [114]. Changes in plasma lactate during an oral glucose tolerance test (OGTT) are inversely correlated with fasting insulin, indicating that IR can be reflected through this metabolite response to a glucose challenge [115,116]. Lactate homeostasis is related to glucose metabolism and, therefore, diseases associated with glucose disruption, as MetS, obesity or diabetes, are associated with disturbed lactate metabolism [114,117].…”
Section: Lactatementioning
confidence: 99%
“…Barnett et al proposed that diabetes-associated hyperlactatemia might be an early change in the time course of the disease [39]. Recently, Berhane et al [40] demonstrated that lactate production progressively rises during hyperinsulinemic euglycemic clamp study, a condition of hyperinsulinemia similar to the early stages in the development of T2DM. Intriguingly, similar previous studies also report elevated lactate concentrations during the early stages of diabetes, prediabetes, and the hyperinsulinemia condition.…”
Section: Lactate Production Increases In Diabetesmentioning
confidence: 99%
“…In addition, the postprandially nonoxidative glycolysis is elevated in these patients relative to healthy controls and blood lactate level rises under this condition [36]. Insulin resistance plays a vital role in the pathogenesis of T2DM [46] and can be used as an early marker for the disease [40]. Under the insulin resistant condition, high levels of insulin promote glycolysis through activating two rate limiting enzymes, namely, phosphofructokinase and pyruvate dehydrogenase [47].…”
Section: Lactate Production Increases In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation